Ice, wind, and water: Synoptic-scale controls of circulation in the Chukchi Sea. (December 2021) - Ovall, Bridget; Pickart, Robert S.; Lin, Peigen; Stabeno, Phyllis; Weingartner, Thomas; Itoh, Motoyo; Kikuchi, Takashi; Dobbins, Elizabeth; Bell, Shaun
Highlights: Northeasterly winds reverse the flow in Barrow Canyon. Atlantic Water is most commonly upwelled to the head of Barrow Canyon in winter. Bering Strait inflow influences freeze-up and melt-back of sea ice in Chukchi Sea. The Northeast Chukchi polynya has sensible heat and wind-driven components. There are dominant patterns of coherent flow across the eastern Chukchi Sea. Abstract: A composite dataset of 27 moorings across the Chukchi Sea and Bering Strait in 2013–14, along with satellite sea ice concentration data, weather station data, and atmospheric reanalysis fields, are used to explore the relationship between the circulation, ice cover, and wind forcing. We find a clear relationship between northeasterly winds along the northwest coast of Alaska and reversed flow along the length of Barrow Canyon and at a mooring site ∼ 100 km upstream on the northeast shelf. Atlantic Water is frequently upwelled into the canyon during the fall and winter, but is only able to reach the head of Barrow Canyon after a series of long upwelling events. A pair of empirical orthogonal function (EOF) analyses of ice cover reveal the importance of inflow pathways on the pattern of freeze-up and melt-back, and shed light on the relative influence of sensible heat and wind forcing on polynya formation. An EOF analysis of 25 mooring velocity records reveals a dominant pattern of circulation with coherent flow across the shelf, and a secondary pattern of opposing flow between Barrow Canyon and Bering Strait. These are related to variations in the regional wind field.